Evaluation of Different Insecticidal Schedules against Rice Yellow Stem Borer Scirpophaga incertulas (Walker) - Omprakash, S.; Reddy, S. Srinivasa (International Journal of Economic Plants, 2025)
A field experimental trial was conducted during two consecutive rabi season of 2018–19 and 2019–20 at Regional Agricultural Research Station, Jagtial, Hyderabad, Telangana, India to evaluate different insecticidal schedules against yellow stem borer in rice. The lowest dead hearts incidence was observed in 15–20 days after transplanting(DAT) chlorantraniliprole 0.4 GR @ 4 kg acre-1+50–60 DAT cartap hydrochloride 50 SP @ 400 g acre-1 schedule (0.38%) followed by 15–20 DAT chlorantraniliprole 0.4 GR @ 4 kg acre-1+50–60 DAT cabofuran 3G @ 10 kg acre-1 schedule (0.47%) and 15–20 DAT chlorantraniliprole 0.4 GR @ 4 kg acre-1+50–60 DAT acephate 75% SP @300 g acre-1 schedule (0.56%) where chlorantraniliprole0.4 GR was applied at 15–20 DAT. White ears were lowest recorded in15–20 DAT chlorantraniliprole 0.4 GR @ 4 kg acre-1+50–60 DAT cartap hydrochloride 50 SP @ 400 g acre-1schedule (1.70%) followed by 15–20 DAT carbofuran 3G @ 10 kg acre-1+50–60 DAT cartap hydrochloride 50 SP @ 400 g acre-1 (2.21%). Regarding the yield data and cost benefit ratio of the treatments, highest yield and cost benefit ratio was observed in 15–20 DAT chlorantraniliprole 0.4 GR @ 4 kg acre-1+50–60 DAT cartap hydrochloride 50 SP @ 400 g acre-1 schedule (7213 kg ha-1 and 1:3.87) followed by 15–20 DAT cartap hydrochloride 50 SP @400g acre-1+50–60 DAT chlorantraniliprole 18.5SC @ 60 ml acre-1 schedule (7063 kg ha-1 and 1:3.30), respectively.